Islam di Nusantara pada Abad ke-10 Masehi sebagaimana Tercermin dalam Tinggalan Budaya - Utomo, Bambang Budi (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
Muslim merchants were active as traders from the seventh century. Several archipelago Hindu and Buddhist kingdoms established com-mercial and diplomatic connections with Middle Eastern Islamic rulers. Archaeological evidence pointing to this fact has been found at a shipwreck site in the Java Sea near Cirebon. Among the discovered trade goods were indications of Islam in the form of a stamp-mould with the inscription asmaÃ¢â‚¬â„¢ul husna. Although most of the Indonesian community follow Sunni teaching, in practice at this time in Sumatra and Java there are devotees of SyiÃ¢â‚¬â„¢ah. Archaeological evidence points that Islam entered Southeast Asian archipelago from Persia viaÃ‚Â Gujarat, India. The religion was brought by merchants to Southeast Asia, especially to Indonesia and the Malay peninsula.